2018
DOI: 10.1507/endocrj.ej17-0485
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and immunological assessment of small-for-gestational-age children during one-year treatment with growth hormone: the clinical impact of apolipoproteins

Abstract: Children born small for gestational age (SGA) are at a higher risk for metabolic disorders later in life. In this study, we aimed to characterize young SGA children without catch-up growth and evaluate the effects of GH treatment on endocrinological, metabolic, and immunological parameters. Study design is a one-year single hospital-based study included prospective observation of SGA patients during 12 months of GH treatment. Clinical and laboratory profiles of SGA children at baseline were compared with contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Regarding the role of postnatal growth in resistin levels, the results obtained in studies have also been contradictory. Some authors affirmed that SGA infants presented lower resistin concentrations than AGA infants [63], whereas other authors observed higher values [64]. Korhonen et al [62] did not find an association between resistin concentrations and growth among 6-to 14-year-old former VLBW children.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the role of postnatal growth in resistin levels, the results obtained in studies have also been contradictory. Some authors affirmed that SGA infants presented lower resistin concentrations than AGA infants [63], whereas other authors observed higher values [64]. Korhonen et al [62] did not find an association between resistin concentrations and growth among 6-to 14-year-old former VLBW children.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding resistin concentrations, there are inconsistent findings. Some authors have confirmed higher resistin values in SGA infants [ 39 ], while other authors have observed lower values [ 40 ]. In our research, resistin levels did not show significant differences between the groups.…”
Section: Discussionmentioning
confidence: 97%
“…An earlier analysis by Struwe et al, which included 16 small for gestational age (SGA) and 24 appropriate for gestational age (AGA) children, showed no significant difference between the two groups [ 62 ]. An analysis which compared SGA children at baseline with controls born appropriate size for age showed that resistin levels were lower for SGA children [ 63 ]. On the other hand, another study which included 45 SGA children showed higher levels of resistin, and it was independently correlated with low birth weight [ 64 ].…”
Section: Discussionmentioning
confidence: 99%